Looking Forward, Looking Back - Reflections from SPERA Life Members - Dale, Marie; King, Sheila; Boylan, Colin (Australian and International Journal of Rural Education, 2009)
Australian education has had a long tradition of providing education to children in its rural and remote places. Starting with one teacher schools that were temporary, or provisional or half time in both their operation and nature through to itinerant traveling teachers originally in covered wagons and then motor vehicles leading to the permanent establishment of primary schools in rural locations, every state and territory education authority and rural community have recognised the value and importance of providing education for its children where they live. Yet, in spite of the strong demand for rural schools and staffing operations in each Australian state and territory education system, rural education was the often neglected or treated like the ugly duckling‘ to quote Johnathon Sher‘s words. While teacher unions and teacher professional / curriculum organisations emerged and flourished, there was no equivalent voice for rural education, rural teachers, rural communities and their specific place related concerns.